Understanding India’s Urban Frontier : What is Behind the Emergence of Census Towns in India? - World Bank (Washington, DC, 2015)
According to the latest census of 2011, the urbanization level in India has increased from 27.8 percent in 2001 to 31.2 percent in 2011, and for the first time, the absolute increase in urban population exceeded the increase in rural population. India has different administrative arrangements for rural and urban areas, which are based on the 73rd and 74th amendments to the Constitution of India respectively. Since the census towns (CTs) continue to be governed by rural administrative arrangements this situation raises an additional set of questions, in addition to the nature of economic transformation, related to the trade-offs-between rural and urban status. The report shall try and find answers to the following questions: (a) how does their governance affect the settlements economically and spatially?; (b) what underpins the economic dynamics of these settlements?; and (c) what are the drivers of change in land use and what relationships, if any, are there between agglomeration of settlements and economic and social and governance processes? The report is organized into two main parts. The first part provides a reading of the existing literature on small towns along the three main axis of research: governance, employment, and spatial change. It also provides a detailed rationale for the choice of sites and expands on the methodology chosen. The second part constitutes of four sections: (i) the first considers the CT as a liminal notion, enabling to unpack ones reading of urbanization; (ii) the second is concerned with the shift towards non-farm employment, the reality (or not) of sectoral differentiation in CTs, and the analysis of the new types of jobs existing in the towns; (iii) the third is concerned with the existing debates and practices around the idea that some CTs should become statutory towns; and (iv) the fourth looks at the various urban services and attempts to assess which variations (rural and urban; state) explain differences in services.